Correlations between interfacial tension and cumulative tertiary oil recovery in a triglyceride microemulsion flooding - Jeirani, Z.; Mohamed Jan, B.; Si Ali, B.; Noor, I.M.; See, C.H.; Saphanuchart, W. (Elsevier, 2013)
This paper presents measurements of interfacial tension (IFT) and tertiary oil recovery (TOR) of triglyceride microemulsion flooding over a wide range of aqueous phase compositions. Based on 160 experimental data sets, two empirical correlations were established. Both the power-law and logarithmic models were validated statistically. Power-law and logarithmic models are predicted to perform best at ultralow IFT range (<0.001 mN/m) and high IFT range (>2 mN/m), respectively. The valid models indicate that IFT is the sole parameter affecting the cumulative TOR in a triglyceride microemulsion flooding. This phenomenon, however, does not apply in hydrocarbon-based microemulsions.